Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s42729-020-00284-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Forage Yield and Nutrients with Altitude Gradients and Their Influencing Factors in Alpine Meadow of Sanjiangyuan, China

Abstract: This study aimed to investigate the forage yield and quality and extract factors affecting them and provide scientific support for ecological protection of alpine grassland and sustainable development of animal husbandry in the Qinghai-Tibetan Plateau. Samples were collected in late August (peak of the growing season) 2014 in two mountain transects (Laji mountain, 36°21′ N, 101°27′ E, 3389-3876 m a.s.l. and Heitu mountain, 34°22′ N, 100°30′ E, 4121-4268 m a.s.l.) of Sanjiangyuan. Forage biomass and nutrients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This is consistent with previous reports of Stevia rebaudiana leaves [20]. However, the correlation between biomass and altitude is controversial [21]. Some studies have shown an inverse relationship.…”
Section: Morphological Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous reports of Stevia rebaudiana leaves [20]. However, the correlation between biomass and altitude is controversial [21]. Some studies have shown an inverse relationship.…”
Section: Morphological Characteristicssupporting
confidence: 92%
“…Some studies have shown an inverse relationship. For example, the forage yield decreased significantly with the increasing altitude in Alpine Meadow of Sanjiangyuan, China [21]. More parameters, such as nutrient element in soil, are worth investigating [22].…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…Insignificant changes in calcium content, alkaloid content, saponin content, phosphorus, potassium, and sodium were observed in the study [Table 2] [Figure 2] [87,88]. Crude fiber and crude fat in our study were observed in higher amounts at middle altitude in comparison to the higher and low elevation which was in agreement with the study done on red clover cultivars, where crude fat content was higher in mountain region in comparison to the low land region [1,89] but the outcomes in our study were not statistically significant [Table 1]. In comparison to low altitude, concentration of phenols increased at high altitudes in our study.…”
Section: Resultssupporting
confidence: 90%
“…Geographical regions positioned far from one another possess diverse climatic conditions which thereby impact the production of plant's physiology. An extensive series of environmental aspects change with the varying elevation, for example, plants in high-altitude surroundings are exposed to numerous environmental strains, mainly in temperature and radiation extremes [1]. Elevation could be the main predictor of changes in phytochemical defense strategy of plants [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the alpine area, the effects of climatic variables on vegetation are emphasized by the harsh environmental conditions due to aspect, elevation, and slope. Aspect determines different light exposition, soil moisture, and nutrient availability, thus representing a direct driver of the botanical composition of pastures (e.g., Yanyan et al, 2017) and an indirect factor affecting biomass productivity and its quality (Dongdong et al, 2020). Increasing elevation determines a decrease in air temperature (0.65°C every 100 m) with consequent effects on vegetation productivity (biomass production is generally lower) and growing season length, which is shorter at higher elevation (Dongdong et al, 2020; Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%